Review of Indigenous Education and Sami Pedagogy:Key Tendencies and Notions - Keskitalo, Pigga; Olsen, Torjer (Brill, 2024)
This chapter portrays Sami education as deeply rooted in culturally specific childrearing practices and traditional knowledge passed down from through generations, enduring across diverse institutional settings within Sami educational contexts despite historical challenges, including colonialism. Aligned with global advancements in Indigenous education, Sami education reflects ongoing efforts in cultural revitalisation and asserting cultural sovereignty. It underscores the broader objective shared by Indigenous worldwide: nurturing youth in their distinct cultures, deeply connected to the cosmology, land, and water of each Indigenous community. The chapter highlights Sami education as evolving from colonial state policies to address contemporary and future educational needs while acknowledging the ongoing risk of Sami language loss. It situates Sami educational development within the global discourse on Indigenous education, noting recent institutional enhancements driven by legal support and increased resources, which have catalysed significant changes at educational and societal levels. Challenges remain, including the enduring impact of colonialism and assimilation, underscoring the ongoing imperative to safeguard the well-being of Indigenous children, families, and communities. This chapter portrays Sami education as deeply rooted in culturally specific childrearing practices and traditional knowledge passed down from through generations, enduring across diverse institutional settings within Sami educational contexts despite historical challenges, including colonialism. Aligned with global advancements in Indigenous education, Sami education reflects ongoing efforts in cultural revitalisation and asserting cultural sovereignty. It underscores the broader objective shared by Indigenous worldwide: nurturing youth in their distinct cultures, deeply connected to the cosmology, land, and water of each Indigenous community. The chapter highlights Sami education as evolving from colonial state policies to address ...